Impact of xylene exposure on blood profiles and neurotoxic symptoms among printing workers in Surabaya - Tualeka, Abdul Rohim; Perumal, Velu; Novianti, Salsabila; Putro, Gurendro (Sami Publishing Company, 2025)
Xylene exposure is influenced by worker characteristics and the quality of the work environment. This study aimed to investigate the relationship between xylene exposure, blood profiles, and neurotoxic complaints among printing workers in Surabaya. An observational, cross-sectional design was employed, involving 30 workers who met the inclusion criteria. Data collection methods included questionnaires, documentation, interviews, and measurements. The independent variables were the concentration of xylene in the work environment (used to assess the intake dose) and worker characteristics such as age, years of service, working hours, nutritional status, use of personal protective equipment (PPE), smoking habits, and exercise habits. The dependent variables included blood profiles (erythrocytes, platelets, leukocytes, LDL, and cholesterol) and neurotoxic complaints. The results revealed that xylene concentrations were still below the threshold limit value. A total of 16 workers (53.3%) reported experiencing neurotoxic complaints. Blood profiles (erythrocytes, platelets, leukocytes, LDL, and cholesterol) remained within the normal range. Statistically significant relationships were found between xylene intake dose and neurotoxic complaints, between xylene intake dose and blood profiles, and between worker characteristics and neurotoxic complaints. To mitigate risks, it is recommended that printing companies improve ventilation systems, ensure safe working environments, promote a culture of health and safety, conduct regular health checks, and provide appropriate PPE for workers.